2016
DOI: 10.1073/pnas.1607330114
|View full text |Cite
|
Sign up to set email alerts
|

Mere experience of low subjective socioeconomic status stimulates appetite and food intake

Abstract: Among social animals, subordinate status or low social rank is associated with increased caloric intake and weight gain. This may reflect an adaptive behavioral pattern that promotes acquisition of caloric resources to compensate for low social resources that may otherwise serve as a buffer against environmental demands. Similarly, diet-related health risks like obesity and diabetes are disproportionately more prevalent among people of low socioeconomic resources. Whereas this relationship may be associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
123
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(133 citation statements)
references
References 44 publications
6
123
1
3
Order By: Relevance
“…Recent studies have experimentally induced lower or higher SSS (24, 25). Cheon et al conducted four studies where low (vs. high or neutral) socioeconomic status was experimentally induced in the participants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have experimentally induced lower or higher SSS (24, 25). Cheon et al conducted four studies where low (vs. high or neutral) socioeconomic status was experimentally induced in the participants.…”
Section: Introductionmentioning
confidence: 99%
“…Cheon et al conducted four studies where low (vs. high or neutral) socioeconomic status was experimentally induced in the participants. They observed that the subjective experience of low social class resulted in a preference for high energy foods and increased intake of energy from meals and snacks independent of financial resources (24). Cardel et al also conducted a randomized crossover study in Hispanic young adults to experimentally manipulate social status conditions using a game of Monopoly™.…”
Section: Introductionmentioning
confidence: 99%
“…Again, this is distinct from mentioning the negative mental health impacts of climate change. In discussions of education and behavior, there is no mention of educating the affluent to understand what it 'feels' like to be in poverty [208][209][210]; this is an upstream step that might incentivize policy makers to more viscerally understand how neoliberal 'behaviors' influence the status quo. Moreover, the term living wage (or even the word 'wage' makes no appearance)-which seems odd given its connection to positive mental health and the healthy behaviors, (including healthy dietary patterns and opportunity for recreation) which planetary health is attempting to promote [211][212][213][214][215][216][217][218].…”
Section: Academic Planetary Health Expanding the Discoursementioning
confidence: 99%
“…Research on allostatic load informs us that past experiences in the ecological theatre would prime the individual for higher levels of inflammation and oxidative stress in response to stress. Consider that even the mere researcher-invoked feeling of poverty or belonging to an SES "out-group" (in a laboratory setting) is enough to alter dietary choices in the direction of low-nutrient, high-calorie foods [93][94][95].…”
Section: Dysbiosis and The Mental Environmentmentioning
confidence: 99%